The Peran Nilai Nilai Budaya Organisasi dalam Pelaksanaan Manajemen Perubahan pada PT. Multi Garmenjaya - Salsabila, Annisa; Resya Dwi Marselina (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
This study aims to explain the role of organizational cultural values in the implementation of change management at PT. Multi Garmenjaya, using a qualitative approach with descriptive analysis method this study identifies the role of cultural values in the implementation of change management and cultural values that can reduce resistance to change. The results showed that the role of organizational culture at PT. Multi garmenjaya as a driving factor in the implementation of change management, companies and employees can properly manage the changes that occur, and with a positive organizational culture can eliminate resistance to change. As a suggestion, this research recommends improving the quality of training and development as well as increasing communication and transparency in making changes